2023
DOI: 10.1021/acs.energyfuels.3c02540
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Hg0 Oxidation over a Mn-Doped VWTi Catalyst at a Wide Temperature Window

Wenbo Jia,
Ying Li,
Hao Chang
et al.

Abstract: A series of Mn-doped VWTi (Mn-VWTi) catalysts were prepared and used for simultaneous NO removal and Hg0 oxidation at a wide temperature window of 200–400 °C for the first time, and the catalytic activity of the Mn-VWTi catalysts was investigated. The results indicated that Mn doping could notably improve the NO removal activity at 200–300 °C and the Hg0 oxidation activity at 200–400 °C, and the catalyst with 3% Mn loading exhibited superior catalytic activity. The relationship between NO removal and Hg0 oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…The ratio of O α exhibited slightly decrease after the catalyst pretreated under N 2 /O 2 /Hg 0 , indicating that the Hg 0 oxidation process consumed the chemisorbed oxygen species. Researchers have found that the chemisorbed oxygen species is more active than the lattice oxygen species because of its superior mobility. , Our previous study also found that the chemisorbed oxygen species was responsible for Hg 0 oxidation. , However, the O α ratio increased when the catalyst was pretreated in the presence of NO. This might be because the gaseous NO could adsorb on the catalyst surface to form adsorbed NO or other substance containing O species, thus increasing the chemisorbed oxygen species. , This is also the main reason why NO can promote the Hg 0 oxidation in the presence of O 2 .…”
Section: Resultsmentioning
confidence: 82%
“…The ratio of O α exhibited slightly decrease after the catalyst pretreated under N 2 /O 2 /Hg 0 , indicating that the Hg 0 oxidation process consumed the chemisorbed oxygen species. Researchers have found that the chemisorbed oxygen species is more active than the lattice oxygen species because of its superior mobility. , Our previous study also found that the chemisorbed oxygen species was responsible for Hg 0 oxidation. , However, the O α ratio increased when the catalyst was pretreated in the presence of NO. This might be because the gaseous NO could adsorb on the catalyst surface to form adsorbed NO or other substance containing O species, thus increasing the chemisorbed oxygen species. , This is also the main reason why NO can promote the Hg 0 oxidation in the presence of O 2 .…”
Section: Resultsmentioning
confidence: 82%